Diosgenin induces apoptosis in HeLa cells via activation of caspase pathway - HUO Rui; ZHOU Qiu-li; WANG Ben-xiang; TASHIRO Shin-ichi; ONODERA Satoshi; IKEJIMA Takashi (Acta Pharmacologica Sinica, 2016)
AIM: To investigate the mechanism of diosgenin-induced HeLa cell apoptosis. METHODS: HeLa cell growth was measured by MTT method. Apoptosis was detected by electron microscopy and agarose gel electrophoresis. Ratio of apoptotic cells was measured by APO-BRDU kit. Cell cycle distribution and changes of mitochondrial membrane potential were monitored by flow cytometry. Caspase activities were assayed by caspase apoptosis detection kit. Western blot analysis was used to evaluate the level of mitochondrial Bcl-2 expression. RESULTS: Diosgenin inhibited HeLa cell growth. HeLa cells treated with diosgenin showed typical characteristics of apoptosis including the morphological changes and DNA fragmentation. Caspase family inhibitor (z-VAD-fmk), caspase-9 inhibitor (Ac-AAVALPAVLLALLAPLEHD-CHO), and caspase-3 inhibitor (z-DEVD-fmk) partially prevented diosgenin-induced apoptosis, but not caspase-8 inhibitor (z-IETD-fmk) and caspase-10 inhibitor (z-AEVD-fmk). Diosgenin caused reduction of mitochondrial membrane potential and down-regulated Bcl-2 expression. CONCLUSION: Diosgenin induced HeLa cell apoptosis through caspase pathway.